Amide Alkaloids from Scopolia tangutica - Long, Zhen; Zhang, Yan; Guo, Zhimou; Wang, Lien; Xue, Xingya; Zhang, Xiuli; Wang, Shisheng; Wang, Zhiwei; Civelli, Olivier; Liang, Xinmiao (Planta Medica, 2014)
Four new hydroxycinnamic acid amides, scotanamines A–D (1–4), and seven known alkaloids, including N1,N10-di-dihydrocaffeoylspermidine (5), scopolamine (6), anisodamine (7), hyoscyamine (8), anisodine (9), caffeoylputrescine (10), and N1-caffeoyl-N3-dihydrocaffeoylspermidine (11), were obtained from the roots of Scopolia tangutica. The present study represents the first recognition of hydroxycinnamic acid amides containing putrescine or spermidine in S. tangutica. Compound 1, in particular, contains a moiety resulting from the condensation of nortropinone and putrescine. Compound 2 exhibited moderate agonist activity at the µ-opioid receptor (EC50 = 7.3 µM). Compound 2 was tested in vivo and induced analgesia in mice. The analgesic effect was recorded using the tail-flick assay and was reversed by naloxone.
Keywords: Scopolia tangutica; Solanaceae; alkaloid; hydroxycinnamic acid amide; µ-opioid receptor